Contemporary Russia Policy for the Southern Caucasus - Marabyan, K. P. (Vestnik MGIMO-Universiteta, 2014)
The bilateral relations between Russia on the one hand, and the countries of the Southern Caucasus region on the other hand are examined in the article. The main directions of Russian policy in the Southern Caucasus region are examined there. The article focusses attention to the value of the Southern Caucasus region for Russia and also to the key role of Russia in the Southern Caucasus region. The overview of Russian-Azerbaijani, Russian-Armenian and Russian- Georgian relations is given in the article. Russian relations with unrecognized Nagorno-Karabakh Republic and with partially recognized Abkhazia and South Ossetia are examined in the context of above-mentioned bilateral relations. The Caucasian direction of Russian foreign policy is of great importance in questions of ensuring Russian national security. The Caucasian crisis of2008 showed potential conflictness of the region and safety hazard of Russia. Now other processes proceed already in the region. Armenian intention to join the Customs union, the change of Georgian leadership and signing of the agreement on association with EU by Georgia start new mechanisms of interaction between the region countries on the one hand and Russia on the other hand. The relation format between region republics can be changed. The main purpose of the article is to show Russian role in questions of the South Caucasus regional security. The region has the conflict territories, from which the Nagorno-Karabakh Republic, the Abkhazian Republic and the South Ossetia Republic are distinguished especially. And Russia won't be able to keep aloof in case of escalation of the conflicts around above-mentioned subjects. The vital questions for the region are peace and stability. And Russia plays a key role in these questions.